DEGRADASI HERBISIDA PENDIMETHALIN PADA TANAH YANG BERBEDA KANDUNGAN BAHAN ORGANIK - Baidhawi, Baidhawi (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2013)
The experiment was conducted at glasshouse owned by Faculty of Agriculture Padjadjaran University, Bandung, Indonesia from June until August 2012. The objective of this experiment was to determine the degradation of pendimethalin herbicide in different soilsorganic matter conten . The design experiment used was complete block design with factorial pattern. There were two factors. The first factor was dose of metolachlor herbicide: 0.00, 0.75, 1.5, and 2.25 kg b.a ha-1. The second factor was soil organic matter content: 1.9, 4.40, 5.98, 6.24, and 12.4 %.The experimetn was that result the herbicide doses and soil organic matter contents has affected on rate of degradation pendimethalin herbicide. The lowest rate degradation of pendimethalin was found in soils lower organic matter content and the highest herbicide doses. The highest rate of degradationwas found in bioassay technique, and HPLC (High perfomance liquid Cromatographi) technique was lowest.